Att göra sig anställningsbar: Om instrumentella identitetspositioner och könad säljbarhet (Sociologisk Forskning, 2011)
To make oneself employable – instrumental identity positions and gendered marketability.The article takes up the question of the negotiation of expert discourses in career advice and constructing the self in the practice of CV writing. Drawing on data from semi-structured interviews with 19 students (11 women and 8 men) the stories about job search are analyzed. The concept of discursive positioning is used in order to analyze how the students position themselves in relation to career advice and position the self in CV writing. The results show that the female students had difficulties embodying the position as a marketing self as they described it as conflicting with feelings of ‘who they were’. ‘Being you’ in CVs and job interviews is, further, an ideal that is negotiated in relation to what to display as a job-seeking subject. CV writing involves a process of identifying suitable characteristics in an instrumental manner, but it is also combined with an introspective reasoning and identification to find ‘authentic’ strengths and characteristics in ‘who you are’.